Pesan pemimpin kaum muslimin sedunia Imam Khamenei pada konferensi kebangkitan Islam - Imam Khamenei (International Affairs Departement, The Institute for Compilation and Publication of Imam Khomeini's World, 2011)
tr,8/ws.c.1-8